2005
DOI: 10.1207/s15327590ijhc1803_2
|View full text |Cite
|
Sign up to set email alerts
|

Use Contexts for the Mobile Internet: A Longitudinal Study Monitoring Actual Use of Mobile Internet Services

Abstract: The mobile Internet, which gives access to the World Wide Web through a mobile device, has been gaining in popularity. The mobile Internet differs from the traditional stationary Internet in that it can be used in a wider variety of contexts. However, no studies have identified the contexts in which mobile Internet services are used most frequently, or determined which contexts exert significant influence on a user's choice of mobile service. This article proposes a framework of use contexts that reflects the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
116
0
3

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(120 citation statements)
references
References 47 publications
1
116
0
3
Order By: Relevance
“…Similarly, Kakihara and Sørensen [20] postulate contexts as continuous frames for people's interaction with others. A more structured definition is provided by [21,22] who categorize context to physical environment and human/personal factors and provide more detailed subgroups within these categories. Belk [23] defined five categories of different situational characteristics including (1) physical context, (2) social context, (3) temporal context, (4) task definition specifying the task at hand and the role in which the task is performed; and (5) antecedent states defined by momentary moods or momentary conditions such as loose change available.…”
Section: Mobility and Mobile Use Contextmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, Kakihara and Sørensen [20] postulate contexts as continuous frames for people's interaction with others. A more structured definition is provided by [21,22] who categorize context to physical environment and human/personal factors and provide more detailed subgroups within these categories. Belk [23] defined five categories of different situational characteristics including (1) physical context, (2) social context, (3) temporal context, (4) task definition specifying the task at hand and the role in which the task is performed; and (5) antecedent states defined by momentary moods or momentary conditions such as loose change available.…”
Section: Mobility and Mobile Use Contextmentioning
confidence: 99%
“…They conclude that technologies designed for mobile computing should be more flexible and adaptable to support tasks in altering environments. Lee et al [21] studied use contexts for mobile Internet services in Korea and found that contextual factors had significant correlations with specific types of mobile services. They further found that mobile Internet use was centered around a few key services and contexts.…”
Section: Mobility and Mobile Use Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…Cui and Roto [5] examined users' mobile web access logs, and found that mobile web use could be classified into four categories: information seeking, communication, transactions, and personal space extension. Lee et al [6] conducted a diary study in which users documented their experiences when using the mobile web, and found that users viewed a variety of sites in a variety of contexts. Other studies [7,8] have identified mobile search patterns from web search query logs.…”
Section: Mobile Web Usementioning
confidence: 99%
“…They do not relate to mobile use context but look the same at home, on the bus, in a café, or walking down the street -situations with very different requirements (e.g. [24]). If we want to bridge the gap between interest and actual use of the mobile Internet, we must do better.…”
Section: The Mobile Internet and Location-based Servicesmentioning
confidence: 99%